Pendidikan yang Memerdekakan, Memanusiakan dan Berpihak pada Murid - Silvia Wardani; Masduki Asbari; Kholid Ibnu Misri (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to find out about the new innovation from the Minister of Education and Culture, namely the Driving Teacher Program, which is expected to be able to produce as many agents of transformation as possible in the educational ecosystem who are able to produce students with global competence and Pancasila character. This study report uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's YouTube channel entitled "Siniar #PojokDikbud: Education that is liberating, humanizing and pro-student." which was explained by the host named Dea Rizkita and the resource person, namely the Director General of Teachers and Education Personnel, Mr. Iwan Syahril. The results of this study explain that the Teacher Mobilization Program is a program to create an education that is liberating, humanizing and pro-student. As an educator, you must be a role model, you must motivate, and you must be an empowerer. The empowerment must lead to the independence of the students. Judging from the KEMENDIKBUD logo "Tut wuri handayani" this is a commitment that as a teacher we must create independent human beings, which is actually what is desired by the philosophy of the Father of our education, namely Mr. Ki Hajar Dewantara, which is very appropriate in our current era.